ASPECTS OF DEVELOPING STUDENTS' PROFESSIONAL COMPETENCE THROUGH PROBLEM-BASED EDUCATIONAL TECHNOLOGIES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article clarifies the main aspects of professional competence and its development in the educational process. Special attention is paid to how the emotional, social relations and leadership components of professional competence in mathematics education are developed through problem-based educational technologies.